STOCK MANAGEMENT SYSTEM FOR RESTAURANT - Nik Mohd Hashim, Nik Nur Lydia (IRC, 2019)
Stock management for a restaurant is very essential. There are many elements to be considered in maintaining the long-term sustainability of the company. For example, the strategy of attracting clients, maintaining the worker, and the financial cost of operating the company and handling the stock. Sometimes stocks will eventually be used up to prepare the meals, and they need to be added. Each meal item is connected to the corresponding resources, ingredients , and the ingredients used to make that dishes are also used as each product is marketed. These stock modifications are tracked using a database. The need of the proper system to keep track stocks in restaurant, the Stock Management System will be developed. The system is important to ease the work of restaurant owner from counting the stock and check whether it tally with the sales manually. This systematic system has functionality where it can know how many ingredients used based on what customer order from the menu. The system also can notify the user when the stock reach critical value and auto restock the stocks from supplier.